AKURASI INSPEKSI VISUAL ASAM ASETAT PADA LOW SQUAMOUS INTRAEPITHELIAL LESIONDIBANDINGKAN DENGAN KOLPOSKOPI DI POLI GINEKOLOGI RS M.DJAMIL PADANG - Vera Nirmala; Desmiwarti Desmiwarti; Hafni Bachtiar (Andalas Obstetrics And Gynecology Journal, 2019)
LSIL is a low grade cervical cancer prelesion, which through prompt diagnosis and therapy, could reduce cervical cancer incidence to 90% and reducing mortality rate for 70-80%. Colposcopy will speed up diagnosis of cervical precancer lesions thus gaining prompt management, and beneficial for patients from afar. Combination of Pap’s smear, colposcopy and biopsy is a good diagnostic package to perform in medical practice. This study was conducted using statistics diagnostic test with cross-sectional design. This research was carried out among women diagnosed with LSIL (Pap’s smear) which then colposcopy was performed in Gynaecology Clinic in Dr.M.Djamil Hospital Padang, during July to December 2014. The study was performed to determine the definitive diagnosis of LSIL (Pap’s smear). Total number of women included in this study were 70, which were divided into 2 groups: 35 women in VIA positive group and 35 in VIA negative group and statistical anal- ysis was performed using unpaired t test and chi square in SPSS 18.0 for windows. From statistical analysis using chi-square test, obtained a statistical significance between VIA test and colposcopy, it can be seen from the p-value 0.002 (p <0.05). There is a statistical significance between VIA test and colposcopy.Keywords: VIA, colposcopy, LSIL, biopsy